The 10th Costal Cartilage Graft in Secondary Cleft Rhinoplasty—A Versatile Rib - Ujam, Atheer B.; Vig, Navin; Nasser, Nasser (Facial Plastic Surgery, 2022)
Autologous costal cartilage for rhinoplasty is an excellent graft material providing both volume and quality of cartilage required for nasal reconstruction. Commonly, the 5th, 6th, 7th, and 8th rib costal cartilages have been harvested but other ribs such as the 10th rib are often overlooked and yet offer an excellent graft option for columellar, alar rim, nasal tip, and dorsal augmentation grafts. The use of the 10th rib costal cartilage in patients with complex secondary cleft nasal deformity has scant reference in the literature. We demonstrate our simple and quick 10th rib cartilage harvesting technique and elicit its use in secondary rhinoplasty and cleft lip nasal deformities. The advantages of harvesting the 10th rib cartilage and our long-term results demonstrating ease of harvest, stability, and predicable outcomes are with several clinical cases. The senior author has used the 10th rib graft successfully in a variety of challenging secondary cleft rhinoplasty procedures with excellent and consistent outcomes. We advocate the use of the 10th rib graft in such procedures as it is easy to harvest, is a dynamic cartilage graft, and offers predictable results with low levels of complications.
Keywords: 10th rib cartilage graft; rhinoplasty; cartilage